From Active Learning to Innovative Thinking: The Influence of Learning the Design Thinking Process among Students - Martina Baričević; Ljerka Luić (MDPI AG, 2023)
Active learning is a set of activities that allow the student to actively participate in the learning process. Active learning can be implemented using various methods and strategies. design thinking is a creative human-centric approach used for innovation. In this article, the authors consider learning the design thinking process as a strategy for active learning. After performing a thorough literature review, the authors display the results of pilot research conducted with business economics graduate students enrolled in the Disruptive Innovations and Design Thinking elective course. The research consisted of a survey and an experiment, and it was executed as part of the project "a/AR-Learning: Active learning by applying augmented reality". The goal was to study the effects of learning the design thinking process and whether it could be used as an active learning method in order to influence the development of innovative thinking among students. The research question was, "How does learning the design thinking process affect the development of students' innovative way of thinking?" The results of the pilot study confirmed all three hypotheses (H1 = After learning the design thinking process, students recognize the main characteristics of innovation; H2 = Active learning of the design thinking process affects critical assessment; H3 = The innovative way of thinking developed through active learning of the design thinking process differs among students), as well as showing effectiveness and a change in critical assessment, but also the need for an even more active approach. The authors suggest that broader research be undertaken involving a bigger sample and a larger scale.